اختراق تكنولوجيا المعلومات المتطورة المجال التعليمي - قداري، أحمد; طيب، سعيدة (جامعة عمار ثليجي الأغواط - مخبر التمكين الاجتماعي والتنمية المستدامة في البيئة الصحراوية, 2019)
نهدف من خلال هذه الورقة البحثية إلى دراسة الاستراتيجيات المناسبة لتفعيل دور تكنولوجيات المعلومات في مجال التعليم والبحث العلمي، من خلال التأقلم والتكيف مع العصرنة واستغلال تقنيات متطورة تسهل الحصول على المعلومة سهلة ومتاح للجميع وفي كل وقت واقل جهد وبأكبر فائدة. حيث يعتبر مفتاح التطور والازدهار لكل دولة اهتمت بمجال التعليم العالي والبحث العلمي، وأهمها أيضا التوجه نحو تبني سياسة وطنية في مجال المعلومات عن طريق تعميم استخدام تكنولوجيات المعلومات في كل القطاعات وخاصة التعليم العالي والبحث العلمي مثل التوجه نحو التعليم عن بعد والافتراضي والجامعة الافتراضية، وتعميم استخدام الإنترنت في المؤسسات البحثية، وكلها عناصر أساسية للتوجه نحو مجتمع المعلومات. The aim of this paper is to study the appropriate strategies to activate the role of information technologies in the field of education and scientific research through adaptation and adaptation to modernity and the exploitation of advanced technologies that facilitate easy access to information and are available to all, at all times and with the least effort and the greatest benefit. Where the key to the development and prosperity of each country is concerned with the field of higher education and scientific research, and the most important is the tendency to adopt a national policy in the field of information through the generalization of the use of information technologies in all sectors, especially higher education and scientific research such as the orientation towards distance and virtual education and virtual university, The Internet in research institutions, all of which are essential elements of the orientation of the information society.
Keywords: تكنولوجيا المعلومات -- تكنولوجيا التعليم -- التعليم الإلكتروني -- البحوث العلمية